Zustand und Entwicklung ausgewählter Fischbestände Einschätzung und Empfehlungen des ICES im Jahr 2004 - Zimmermann, Christopher; Gröhsler, Tomas (2004)
The state of North Atlantic, Baltic Sea and North Sea commercially exploited fish stocks are assessed annually by the International Council for the Exploration of the Sea (ICES). Estimates of the stock size (biomass), recruitment, landings, current exploitation rates and of future harvesting possibilities are provided for those stocks where sufficient information is available to conduct a full analytical assessment. For all other stocks, only landings and stock trends can be given. This paper presents the development of north-east Atlantic fish stocks which are of general or specific interest for the German fishery and fish industry. Generally, it may be concluded that most pelagic fish stocks, such as herring, sprat, mackerel, and blue whiting, are in good condition, while the majority of the demersal stocks, like cod, plaice or whiting are in critical state. There are, however, a number of remarkable exceptions to this pattern.